Problems of the Assessment of Economic Damage Caused by Power Supply Interruption - Lesnykh, Valery Vitalyevich; Timofeyeva, Tatiana Borisovna; Petrov, Vladislav Sergeevich (Economy of Regions, 2017)
Pie article is devoted to the development of the methods of the assessment of damage caused by an emergency interruption in the electrical supply of industrial consumers. The purpose of the study is to substantiate the structure of direct and indirect damage and to develop an adequate technique for the quantitative assessment of a full damage caused by the interrupt in electrical supply of various groups of industrial consumers. The analysis of domestic and foreign methodological approaches to the assessment of the damage caused by breaks in an electrical supply allowed to substantiate the structure of a full damage. For this purpose, we propose three groups of techniques. The first method is based on the standard approach. We apply it for a detailed account of the components of damage (real loss, social and economic losses, ecological damage, indirect losses) with reference to the occurred failure. The second technique is based on the use of three groups of typical scenarios of the consequences of an emergency interruption in power supply. These scenarios have resulted from the analysis of the regulation documentation and statistical data on the basic groups of industrial consumers (on the example of gas supply system, these are production facilities, transport, storage, reprocessing and support facilities). The third method is based on the specific indicators of unplanned coasts depending on the size of the disconnected capacity, an interruption duration and the duration of the restoration of electricity. The second and third techniques are developed to forecast the damage and to substantiate the efficiency of measures for improving the reliability of the electrical supply of the industrial consumers. The article includes the results of the assessment of full damage caused by the interruption in the electrical supply through the developed techniques on the example of the gas industry objects. The comparison of the results of the assessment with the real values of damages from the occurred failures would suggest the adequacy of the developed techniques. The appropriate account of the economic damage caused by breaks in the electrical supply would substantiate the measures making energy supplies for the safe and reliable. The reliability of power is the fundamental factor for the economic stability of the country and its regions.